Engineering standards for trauma and orthopaedic implants worldwide: a systematic review protocol. Issue 10 (18th October 2018) - Henshaw, Frederick; Karasouli, Eleni; King, Richard; Rahman, Usama; Langton, David; Madete, June; Otsyeno, Fred; Mutiso, Vincent; Atinga, John; Underwood, Martin; Williams, Mark; Metcalfe, Andrew
Abstract : Introduction: Despite multiple scandals in the medical implant sector, premarket testing has been the attention of little published research. Complications related to new devices, such as the DePuy Articular Surface Replacement (ASR, DePuy Synthes, USA), have raised the issue of how designs are tested and whether engineering standards remain up to date with our understanding of implant biomechanics. Despite much work setting up national joint registries to improve implant monitoring, there have been few academic studies examining the premarket engineering standards new implants must meet. Emerging global economies mean that the markets have changed, and it is unknown to what degree engineering standards vary around the world. Governments, industry and independent regulatory bodies all produce engineering standards; therefore, the comparison of surgical implants across different manufacturers and jurisdictions is difficult. In this review, we will systematically collate and compare engineering standards for trauma and orthopaedic implants around the world. This will help inform patient, hospital and surgeon choice and provide an evidence base for future research in this area. Methods and analysis: This protocol is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol (PRISMA-P) guidelines. We will conduct a systematic review of trauma and orthopaedic engineering standards from four main sources of information as identified in our preliminary scoping searches: governments, industry, independent regulatory bodies and engineering and medical publications. Any current standard relevant to trauma and orthopaedic implants will be included. We will use a predefined search strategy and follow the recommendations of the Cochrane handbook where applicable. We will undertake a narrative synthesis with qualitative evaluation of homogeneity between engineering standards. Ethics and dissemination: No ethics approval is required as no primary data are being collected. The results will be made available by peer-reviewed publication and reported according to PRISMA-P guidelines.